ANALISIS ATENSI VISUAL CALON MAHASISWA PADA BROSUR PERGURUAN TINGGI MENGGUNAKAN METODE EYE TRACKING - Dede Febrian Saragih Sumbayak; Muhammad Baihaqi Siregar; Deni Adha Akbari; Rizki Edmi Edison; Evta Indra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The purpose of the research is to analyze the figures presented in the E-Brochure of the Faculty of Science and Technology at Prima Indonesia using the eye movement patterns of prospective students, to find out if the people displayed represent each study program. The problem is in the 2022 to 2023 academic year was a decrease in the new students by 30%, especially in the Faculty of Science and Technology. Therefore, more specific research must be carried out on the use of E-Brochures to improve the quality of promotions. The visual attention patterns of 80 prospective students were recorded using eye-tracking technology to find out their objective assessment of the figures displayed. The research results indicated a variation in participant’s visual focus on different Regions of Interest (RoI) for each image. For example, in image 1, RoI 3 received the most attention with a dwell time of 2.43 seconds, while in image 2, RoI 2 was the main focus with a dwell time of 1.41 seconds. This data suggests that facial elements tend to attract more attention than properties, although there are exceptions depending on the image's composition. The benefit of this research is improving the quality of the E-Brochure of the Faculty of Science and Technology, Prima Indonesia University so that it pulls the interest of new students.